The increase in the use of psychotropic drugs during the pandemic in Brazil: Literature review (Research, Society and Development, 2024)
This study aims to analyze the increase in the use of psychotropic drugs during the COVID-19 pandemic in Brazil, highlighting its relationship with the impact on the population's mental health between March 2020 and September 2021. A bibliographic review was carried out with searches for scientific articles in the Scielo, LILACS, PubMed and Google Scholar databases, focusing on evidence about the increased use of medications to treat mental disorders during the pandemic. Inclusion and exclusion criteria were applied to select papers closely related to the topic. Analysis of the data revealed a significant increase in the consumption of psychotropic drugs, with an increase of up to 113% in the demand for drugs for anxiety, depression and insomnia. This increase is associated with factors such as stress, unemployment and emotional losses resulting from social isolation. The increase in the use of psychotropic drugs during the pandemic reflects a worrying intensification of mental health problems in the Brazilian population. This scenario highlights the urgent need to raise awareness about proper prescribing and the risks of self-medication, which have become common in times of crisis. The situation demands attention from health professionals and authorities to adequately address emerging mental health challenges.